Deep mutational scanning: A versatile tool in systematically mapping genotypes to phenotypes - Wei, Huijin; Li, Xianghua (Frontiers in Genetics, 2023)
Unveiling how genetic variations lead to phenotypic variations is one of the key questions in evolutionary biology, genetics, and biomedical research. Deep mutational scanning (DMS) technology has allowed the mapping of tens of thousands of genetic variations to phenotypic variations efficiently and economically. Since its first systematic introduction about a decade ago, we have witnessed the use of DMS in many research areas leading to scientific breakthroughs. Also, the methods in each step of DMS have become much more versatile thanks to the oligo-synthesizing technology, high-throughput phenotyping methods, and deep sequencing technology. However, each specific possible step of DMS has its pros and cons, and some limitations still await further technological development. Here, we discuss recent scientific accomplishments achieved through the DMS and describe widely used methods in each step of DMS. We also compare these different methods and analyze their advantages and disadvantages, providing insight into how to design a DMS study that best suits the aims of the readers’ projects.